Relation of Antral Follicular Count and Follicular Stimulating Hormone with Anti-Mullerian Hormone in Determining Ovarian Reserve in Infertile Women Presenting in a Tertiary Health Centre of Nepal - Ojha, Bhuwan Prasad; Ghimire, Asmita; Panta, Padam Raj; Ojha, Neebha (Birat Journal of Health Sciences, 2022)
Introduction: Infertility is a disorder of the reproductive system defined by failure to achieve a clinical pregnancy after 12 months or more of regular unprotected sexual intercourse. Globally, about 10-15% married couples are sub-fertile. 20-40% of female factors for infertility include ovarian cause. Ovarian reserve refers to the size of resting primordial follicle in the ovaries which determines the capacity of the ovary to provide egg cells for fertilization resulting in a successful pregnancy. Ovarian reserve is one of the most reliable investigations to determine ovarian regression, which regresses with age. Follicular Stimulating Hormone (FSH), Estradiol (E2), Antral Follicular Count (AFC) and Anti-Mullerian Hormone (AMH) are investigations to determine ovarian reserve. Objective: To determine the correlation of antral follicular count and follicular stimulating hormone with anti-mullerian hormone in determining ovarian reserve among infertile women attending infertility clinic of Tribhuvan University Teaching Hospital (TUTH). Methodology: This was a prospective, hospital based study conducted among 78 patients attending infertility clinic in the Department of Obstetrics and Gynecology at TUTH, Kathmandu from 14th April 2017 to 13th April 2018. After taking history and examination, routine infertility investigation was sent. On the Day 2 or Day 3 of the cycle, serum FSH and AMH were sent. On the 3-5 day of the cycle, trans-vaginal scan was done for antral follicular count. Follicular monitoring was done every alternate day from day 9 of natural cycle till the follicle became 18 to 22 mm. If no follicle developed even after day 20 of menstruation, monitoring was stopped and development of follicle or failure was noted. This monitoring was done in single cycle. Early follicular phase serum FSH, AMH and AFC were correlated in relation to follicular development. Result: Among 78 patients included, mean age was 27.6 ± 3.14 years. The mean FSH, AMH and total AFC were 6.46 ± 1.90 IU/ml, 5.01 ± 3.46 ng/ml and 15.88 ± 5.21 respectively. A strong positive linear correlation between AFC and AMH (p<0.001, r=0.811) and weakly negative correlation between FSH and AMH (p=0.182, r= -0.153) was found. Conclusion: Serum AFC level showed a strong positive correlation with AMH and could be used as an alternative to AMH to assess ovarian reserve.